Detecting children's false allegations and recantations of a crime - Wyman, Joshua (Psychology, crime & law, 2018)
This study examined adults’ abilities to detect the veracity of children's (ages 6-11) initial disclosures and their later recantations about a crime. Children (N = 32) were asked to make a false denial or a false accusation of an alleged theft, while some were asked to tell the truth. Afterwards, children recanted their initial statements in a second interview; thus, children who initially denied the theft accused a researcher of the transgression in the second interview, and vice-versa. Adult raters (ages 18-25; N = 108) watched both interviews and completed a questionnaire that required them to determine the veracity (i.e. whether the report was true or false) and credibility of the disclosure. Adults accurately detected the veracity of children's reports 53% of the time (55% of original reports, 50% of recantations). Raters were more accurate when detecting false denials than false accusations in the children's original and recanted reports. Despite being more difficult to detect, children's recanted denials that became accusations were rated as the least credible. Furthermore, self-reported level of experience with children and ratings confidence were not significant predictors of truth/lie detection accuracy.